Temperature Reactivity Control of Calcium Hydride–Moderated Small Reactor Core with Poison Nuclides. (2nd September 2019) - Kimura, Rei; Wada, Satoshi
Abstract: A small modular reactor (SMR) is a promising candidate for future nuclear energy; therefore, many organizations are developing SMRs. Some SMRs have a power output higher than 100 MW(electric). This paper, however, describes a much smaller reactor of less than 10-MW(electric) power output: a microreactor. The microreactor shares the same advantages as SMRs, i.e., passive safety, portability, and maintainability. This paper studies a calcium hydride (CaH2 ) heat pipe–cooled reactor in which heat pipes and CaH2 accomplish passive removal of generated heat, fuel inventory reduction, high-temperature operation, and prevention of a loss-of-coolant accident. The CaH2 allows operation at a core temperature of 800°C, which improves the efficiency of the reactor system. In the case of moderator function loss, hydrogen dissociation may occur at the higher temperature; however, negative temperature reactivity of the hydride-moderated core prevents reactor runaway. The negative temperature reactivity is realized by the poison nuclides 113 Cd and 151 Eu, which have a capture resonance peak at thermal energies in high-temperature operation. It was confirmed that the proposed method is capable of controlling the reactor over the whole burnup period.